CNN Based Handwritten Devanagari Digits Recognition - Kumar, Gaurav; Kumar, Sachin (International Journal of Computer Sciences and Engineering, 2025)
Handwritten Digit Recognition has huge demand in commercial, administrative and academic domains. In recent years lot of good work has been done to improve accuracy of Handwritten Digit Recognition System but accuracy of such systems depend on large datasets. Deep Convolutional Neural Network have shown superior results to traditional shallow net-works in many recognition task. In this paper, a convolutional neural network (CNN) based Devanagari digit recognition system is highlighted. The dataset contains 21969 hand written 28x28 size images. The result of proposed system showed 99.07% accuracy on our dataset.